The Immediate Pulmonary Disease Pattern following Exposure to High Concentrations of Chlorine Gas - Balte, Pallavi P.; Clark, Kathleen A.; Mohr, Lawrence C.; Karmaus, Wilfried J.; Van Sickle, David; Svendsen, Erik R. (Pulmonary Medicine, 2013)
Background. Classification of pulmonary disease into obstructive, restrictive, and mixed patterns is based on 2005 ATS/ERS guidelines and modified GOLD criteria by Mannino et al. (2003), but these guidelines are of limited use for simple spirometry in situations involving mass casualties. Aim. The purpose of this study was to apply these guidelines to patients who underwent simple spirometry following high concentration of chlorine gas inhalation after a train derailment in Graniteville, South Carolina. Methods. We retrospectively investigated lung functions in ten patients. In order to classify pulmonary disease pattern, we used 2005 ATS/ERS guidelines and modified GOLD criteria along with our own criteria developed using available simple spirometry data. Results. We found predominant restrictive pattern in our patients with both modified GOLD and our criteria, which is in contrast to other chlorine exposure studies where obstructive pattern was more common. When compared to modified GOLD and our criteria, 2005 ATS/ERS guidelines underestimated the frequency of restrictive disease. Conclusion. Diagnosis of pulmonary disease patterns is of importance after irritant gas inhalation. Acceptable criteria need to be developed to evaluate pulmonary disease through simple spirometry in events leading to mass casualty and patient surge in hospitals.